Recent Advances in Computational and Experimental Mechanics, Vol II Select Proceedings of ICRACEM 2020 - Maiti, D. K.; Jana, P.; Mistry, C. S.; Ghoshal, R.; Afzal, M. S.; Patra, P. K.; Maity, D.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book (Vol. II) presents select proceedings of the first Online International Conference on Recent Advances in Computational and Experimental Mechanics (ICRACEM 2020) and focuses on theoretical, computational and experimental aspects of solid and fluid mechanics. Various topics covered are computational modelling of extreme events; mechanical modelling of robots; mechanics and design of cellular materials; mechanics of soft materials; mechanics of thin-film and multi-layer structures; meshfree and particle based formulations in continuum mechanics; multi-scale computations in solid mechanics, and materials; multiscale mechanics of brittle and ductile materials; topology and shape optimization techniques; acoustics including aero-acoustics and wave propagation; aerodynamics; dynamics and control in micro/nano engineering; dynamic instability and buckling; flow-induced noise and vibration; inverse problems in mechanics and system identification; measurement and analysis techniques in nonlinear dynamic systems; multibody dynamical systems and applications; nonlinear dynamics and control; stochastic mechanics; structural dynamics and earthquake engineering; structural health monitoring and damage assessment; turbomachinery noise; vibrations of continuous systems, characterization of advanced materials; damage identification and non-destructive evaluation; experimental fire mechanics and damage; experimental fluid mechanics; experimental solid mechanics; measurement in extreme environments; modal testing and dynamics; experimental hydraulics; mechanism of scour under steady and unsteady flows; vibration measurement and control; bio-inspired materials; constitutive modelling of materials; fracture mechanics; mechanics of adhesion, tribology and wear; mechanics of composite materials; mechanics of multifunctional materials; multiscale modelling of materials; phase transformations in materials; plasticity and creep in materials; fluid mechanics, computational fluid dynamics; fluid-structure interaction; free surface, moving boundary and pipe flow; hydrodynamics; multiphase flows; propulsion; internal flow physics; turbulence modelling; wave mechanics; flow through porous media; shock-boundary layer interactions; sediment transport; wave-structure interaction; reduced-order models; turbo-machinery; experimental hydraulics; mechanism of scour under steady and unsteady flows; applications of machine learning and artificial intelligence in mechanics; transport phenomena and soft computing tools in fluid mechanics. The contents of these two volumes (Volumes I and II) discusses various attributes of modern-age mechanics in various disciplines, such as aerospace, civil, mechanical, ocean engineering and naval architecture. The book will be a valuable reference for beginners, researchers, and professionals interested in solid and fluid mechanics and allied fields.
Chapter 1: Baseline Free Damage Localization in Beam-like Structures using Teager-Kaiser Energy Operator -- Chapter 2: Comparative Study on the Effectiveness between Shear Wall and Bracing Systems on High-rise Structures -- Chapter 3: Dynamic stresses in bridge girder caused by the randomly moving loads -- Chapter 4: A Comparative Study on the Vibration Control of a Bridge under Moving Springing Mass by TMD and TMDI -- Chapter 5: A numerical approach to model heterogeneity of concrete in RC beam subjected to impact loading.
Keywords: Fluid mechanics; Mechanics, Applied; Solids; Multibody systems; Vibration; Engineering Fluid Dynamics; Solid Mechanics; Multibody Systems and Mechanical Vibrations; Mechanics, Applied -- Congresses; Dynamics -- Congresses